Clinical and morphological aspects of Listeria infection in the system «mother-placenta-fetus». - I. V. Sorokina; M. S. Myroshnychenko; O. M. Pliten; O. A. Omelchenko; O. V. Kaluzhina; A. V. Simachova; I. S. Zvereva (Морфологія, 2016)
Listeriosis is an infectious disease characterized by numerous sources of infection, variety of factors and transmission routes of the pathogen, polymorphic clinical picture. Listeriosis is particularly dangerous for pregnant women. The purpose of the work was the analysis of literature data about Listeria infection in the system «mother-placenta-fetus» and own cases from practices of Listeria infection in one fetus and four newborns. In own cases from practice the authors noted that the specific macroscopical and microscopical changes typical for Listeria infection were absent, however, considering the positive results of bacteriological examination of biological material, pathologist was forced to put a major disease in four cases the congenital bronchopneumonia of listeriosis genesis, and in one case – intrauterine hypoxia caused by violation of utero-placental circulation due to the presence of Listeria infection in the mother. In all cases during histological study of the placenta it was revealed not only purulent inflammation, but also the signs of chronic placental insufficiency, due to the presence of Listeria infection in maternal organism, which has led to the development of chronic intrauterine hypoxia, the occurrence of prematurity and intrauterine growth retardation of fetus or newborn. The authors hope that this article will be interesting for doctors of different specialties.